Measurement of Motor Vehicle Emissions Based on Low-cost Sensors - Kurniawan, Michelle; Ardiles, Sopaheluwakan Alesandro; Adiwidya, Andre Suwardana; Ummi, Annisa Zahwatul; Halinda, Maulana Fauzan Athalla; Okthaviany, Indah Cikal Al Gyfary; Gajah, Deni Ali Marwan; Hidayat, Putri Naila Alyana; Lalintia, Irvin Judah; Kampong, Prichel Adisatya; Salam, Rahmat Awaludin; Chandra, Indra (Universitas Telkom, 2023)
One of Indonesia's primary causes of air pollution is the significant level of human activity, particularly the continued use of fossil-fuel-powered vehicles. The incomplete combustion of fossil fuels can lead to gas and particle pollutants forming, impacting the environment. However, the instruments utilized for detecting environmental pollutants are relatively expensive. Therefore, motor vehicle emission tests use low-cost sensors with parameters such as CO, CO2, NO2, PM2.5, temperature, and RH. The flow rate measures the emission gas flow extracted from a vehicle's exhaust into the testing chamber and then released into the air for disposal. The flow rate utilized in these tests ranges from 12 to 15 lpm. The tests are conducted over 10 minutes to ensure accuracy, obtaining average readings for the measured parameters. For the measurement results using a low-cost sensor, the average value for CO is 383.891 ppm, NO2 is 10.7237 ppm, CO2 is 5,254 ppm, PM2.5 is 50.25 ?g/m3, temperature and RH is 28.9 °C and 76%. The official test results obtained a CO value of 1,200 ppm, CO2 of 140,000 ppm, and a temperature of 80 °C. This difference is because the reading range of low-cost sensors is relatively small but has a stable data trend.